Texting and the Language of Everyday Deception. Issue 7 (8th August 2020) - Holtgraves, Thomas; Jenkins, Elizabeth
ABSTRACT: Two experiments were conducted to examine the production and detection of common, everyday deception. Experiment 1 was a naturalistic study in which participants provided their most recent truthful and deceptive (both sent and received) text messages. Participants in Experiment 2 were asked to generate text messages that were either deceptive or truthful. Messages in both experiments were analyzed with the Linguistic Inquiry and Word Count (LIWC) program and presented to other participants for their judgments of truthfulness. LIWC analyses yielded both similarities (e.g., more negations in deceptive texts) and differences (e.g., more first-person pronouns in deceptive texts) with past deception research. In contrast to prior deception research, participants in both experiments were able to significantly differentiate between deceptive and nondeceptive messages, and some of the LIWC variables that differentiated deceptive from nondeceptive texts were significantly related to judgments of truthfulness.